The incidence of match and training injuries in rugby league: A pooled data analysis of published studies - King, D.; Gissane, C.; Clark, T.; Marshall, S. W. (International Journal of Sports Science and Coaching, 2014)
Studies reporting on injuries in rugby league have shown that the injury incidence increases as the participation level increases. To provide pooled estimates for the incidence of rugby league injuries in match and training activities at all levels of performance and by gender. Searches of PubMed, CINHAL, Ovid, MEDLINE, SCOPUS, ScienceDirect and SportDiscus® databases were performed to identify studies published in English prior to November 2012. Bibliographic searches were also carried out without language restrictions. A pooled analysis of published studies which have reported the incidences of rugby league match and/or training injuries. Two reviewers extracted the study characteristics, numerical data and assessed the quality, by adhering to the protocol for systematic review of observational studies (MOOSE). A total of 34 studies (from 1,422 identified in the initial search) were identified that reported data collection of rugby league injuries that met the inclusion criteria. The data provided information from a total of 5,785 match events totalling 87,185 match exposure hr. and 242,754 training exposure hr. The pooled analysis injury incidence for match injuries was 148 (95% CI: 145 to 150) per 1,000 match hr. The lower limb (69; 95% CI: 67 to 72 per 1,000 match hr.) was the most common injury region recorded. Although contusions were the most common pooled injury type (34.0; 95% CI: 32.3 to 35.8 per 1,000 match hr.) this varied by participation level. The pooled analysis injury incidence for training injuries was 12.6 per 1,000 training hr. The lower limb was again the most common injury region recorded (5.7; 95% CI: 5.1 to 5.8 per 1,000 training injuries) for all training studies and strains (3.1; 95% CI: 2.8 to 3.3 per 1,000 training hours) were the most common training injury type recorded. These findings are indicative of the physical demands placed on players across many levels of participation and in time further additions to this analysis are warranted to provide a more detailed picture of the sport from an injury prevention perspective.